2018
DOI: 10.15632/jtam-pl.56.3.803
|View full text |Cite
|
Sign up to set email alerts
|

3D FE analysis of the behavior of elliptical cracks on orthopedic cement of the total hip prosthesis

Abstract: An explicit analysis conducted on the crack behavior in chirurgical cement (Polymethylmethacrylate -PMMA) used for Total Hip Prosthesis (THP) is of great importance in collecting information about the nature of the phenomenon of loosening of the cement application. The rupture of the orthopedic cement is practically the main cause of this loosening. Understanding different rupture mechanisms give a great value in advancing the durability of the cemented total prosthesis. The purpose of this study is to analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In this study the mechanical properties of the components of the femoral prosthesis were taken from previous work [5,7,9,13,23].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the mechanical properties of the components of the femoral prosthesis were taken from previous work [5,7,9,13,23].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…PMMA has important micro structural heterogeneities such as cavities, and its elastic behavior is greatly affected by the presence of defects that may imply its weakening and cause failure [4,5]. In areas of high concentrations of stress and due to the presence of micro cracks appear after crushing cavities due to patient movement; these micro cracks grow and weld to each other until they form a macro fissure that propagates until the total removal of the prosthesis [6,7]. The notions of elastic linear mechanics of fracture, such as the stress intensity factors, the rate of energy restitution, precisely describes the behavior of cracks in fragile materials whatever the state of the fracture geometry and loading [8] .The use of these concepts can be an effective tool for analyzing the fracture behavior of orthopedic cement, which constitutes a predictive tool of pre/post-evaluation device of cemented acetabular reconstructions.…”
Section: Introductionmentioning
confidence: 99%
“…The crack direction was determined using the strain energy Ouinas et al (2012) made a numerical study on the femoral part based on the dynamic loading effect, the crack propagation in the orthopedic cement, to describe the mechanical behavior of cracks in the total hip prosthesis THP. Benouis et al (2018) investigated the 3D-FE method to analyse the behavior of cracks initiated in the cement binding the femoral stem to the bone. That behavior was studied in terms of changes in the SIFs under modes I, II and III.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis was carried out on various zones of cement along the bone, namely the proximal, medial and distal positions. Benouis et al (2018) investigated the 3D-FE method to analyse the distribution of equivalents stress of von Mises around a cavity located in the bone cement polymethylmethacrylate (PMMA). Results showed that the micro-porosity located in the proximal and distal zone of the prosthesis was subject to higher stress field.…”
Section: Introductionmentioning
confidence: 99%
“…First, the level and distribution of equivalent von Mises stress were analyzed. The behavior of elliptical cracks in different geometries was evaluated (Benouis et al 2018). For the analysis of the fracture behavior of cement containing residual bone as inclusion, it was assumed that the cement contained a pointed pyramidal bone fragment with limited volume.…”
mentioning
confidence: 99%